Fabrication and Optimization of Paper-based Analytical Devices (Pads) for Preliminary Analysis of Sedative-hypnotics (Indian Internet Journal of Forensic Medicine and Toxicology, 2026)
Sedative-hypnotics are frequently encountered in drug-facilitated crimes and overdosage cases due to their rapid pharmacological action, amnesic effects, and ease of administration in beverages or food matrices. Conventional forensic screening techniques such as colour tests and thin-layer chromatography (TLC) remain widely used but comes with limitation including subjectivity, limited sensitivity, and infrastructure dependency. Paper-based analytical devices (PADs) have emerged as promising alternatives offering low-cost, portable, and field-deployable analytical platforms. In the present study, five PAD configurations were fabricated using wax imprinting to generate hydrophobic barriers and hydrophilic microchannels. The devices were systematically optimised by evaluating sample retention efficiency, solvent migration behaviour, reagent-sample interaction, and colour development uniformity. Comparative analysis revealed that channel geometry significantly influenced capillary flow dynamics and analytical performance. Among the tested designs, the PAD incorporating a central rectangular interaction chamber demonstrated superior solvent retention, enhanced colour stability, and improved reproducibility. These devices can be effectively used to detect barbiturates, benzodiazepines, z-drugs, etc. The reaction output can be further interpreted for screening and presumptive examination both in field as well as laboratory. The optimised PAD configuration provides a reliable platform for rapid presumptive screening of sedative-hypnotics and supports the integration of portable colorimetric analysis in forensic field investigations.